Technical Note: Assessment of electromagnetic tracking systems in a surgical environment using ultrasonography and ureteroscopy instruments for percutaneous renal access. Issue 1 (22nd November 2019) - Gomes‐Fonseca, João; Veloso, Fernando; Queirós, Sandro; Morais, Pedro; Pinho, António C. M.; Fonseca, Jaime C.; Correia‐Pinto, Jorge; Lima, Estêvão; Vilaça, João L.
Abstract : Purpose: Electromagnetic tracking systems (EMTSs) have been proposed to assist the percutaneous renal access (PRA) during minimally invasive interventions to the renal system. However, the influence of other surgical instruments widely used during PRA (like ureteroscopy and ultrasound equipment) in the EMTS performance is not completely known. This work performs this assessment for two EMTSs [Aurora ® Planar Field Generator ( PFG ); Aurora ® Tabletop Field Generator ( TTFG )]. Methods: An assessment platform, composed by a scaffold with specific supports to attach the surgical instruments and a plate phantom with multiple levels to precisely translate or rotate the surgical instruments, was developed. The median accuracy and precision in terms of position and orientation were estimated for the PFG and TTFG in a surgical environment using this platform. Then, the influence of different surgical instruments (alone or together), namely analogic flexible ureterorenoscope (AUR), digital flexible ureterorenoscope (DUR), two‐dimensional (2D) ultrasound (US) probe, and four‐dimensional (4D) mechanical US probe, was assessed for both EMTSs by coupling the instruments to 5‐DOF and 6‐DOF sensors. Results: Overall, the median positional and orientation accuracies in the surgical environment were 0.85 mm and 0.42° for PFG, and 0.72 mm and 0.39° for TTFG, while precisions were 0.10 mm and 0.03° for PFG, and 0.20 mm and 0.12° for TTFG, respectively. No significant differences were found for accuracy between EMTSs. However, PFG showed a tendency for higher precision than TTFG . AUR, DUR, and 2D US probe did not influence the accuracy and precision of both EMTSs. In opposition, the 4D probe distorted the signal near the attached sensor, making readings unreliable. Conclusions: Ureteroscopy‐ and ultrasonography‐assisted PRA based on EMTS guidance are feasible with the tested AUR or DUR together with the 2D probe. More studies must be performed to evaluate the probes and ureterorenoscopes' influence before their use in PRA based on EMTS guidance.